Ethyl alcohol from whey through anaerobic fermentation: Project study - Glinoga, Debbie Uy (Animo Repository, 1985)
Four yeast strains namely: candida pseudotropicalis (MNHY-3005), saccharomyces fragilis (2015), kluyveromyces fragilis (MNHY-3022) and (MNHY-3023) were tested on their ability to produce ethyl alcohol from whey via anaerobic fermentation. Each fermentation batch was carried out at temperature range of 30-34C and at an initial pH of 4.5. Seventy two hours of fermentation had been allotted per batch. The first part of the experiment was so design that the inoculum type and size that will give the maximum alcohol yield can be determined. It was found out that kluyveromyces fragilis (MNHY-3023) with an inoculum size of 3% (vol/vol) gave the maximum alcohol yield of 45.7%. It also produced the maximum alcohol concentration of approximately 4.0% (vol/vol). Subjecting the inoculum type and size selected on the basis of maximum alcohol yield to varying substrate concentration, it was found out that a substrate concentration of 7 percent (vol/vol) gave the highest alcohol yield.